MENINGKATKAN AKTIFITAS DAN KETUNTASAN BELAJAR PESERTA DIDIK MELALUI PEMBELAJARAN KOOPERATIF TUTOR SEBAYA KELAS VII MATA PELAJARAN EKONOMI PADA MATERI POKOK TINDAKAN EKONOMI SMP NEGERI 1 PANJI KABUPATEN SITUBONDO SEMESTER GANJIL - Ahmad Hafas Rasyidi (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2014)
Peer Tutor Cooperative Learning utilizes peers to act as a learning information center for other students, whose approach strategy is to form groups. Students are expected to more easily accept and understand subject matter from their more capable peers. This study aims to determine whether the Peer Tutor Cooperative Learning will improve student learning outcomes. This type of research is a classroom action research conducted at SMPN 1 Panji, Situbondo Regency. This research was conducted by researchers who act as economics teachers. This research is focused on class VII-F odd semester with 32 students. The application of the peer tutor cooperative learning model with the basic competence of identifying economic action based on economic motives and principles in various daily activities carried out at SMP Negeri 1 Panji has been quite successful. This can be seen from the enthusiasm and activeness of students during the learning process, and the test results obtained by students increased from the results of the test before the action with the cycle I test. Learning before the classical learning completeness action was 62.50%, while the results of the cycle learning test I achieved classical mastery of 96.88%. And the learning activities of class VII-F students can increase. This can be observed in the percentage of the average score of meetings, namely meeting I 54.2%, meeting II 69.22%, and meeting III 85.31%. This shows that the peer tutor cooperative learning model can improve students' understanding of economic actions, motives and principles so as to improve learning outcomes. Based on the research results, it can be concluded that with Peer Tutor Cooperative Learning can improve student learning outcomes.